Consumo alimentar e anticonsumismo: veganos e freeganos - Juliana Abonizio (Ciências Sociais Unisinos)
This article analyzes veganism and freeganism as life styles made possible provided by consumer society. Considering consumption as a dynamic system of world classification, I notice that such movements, by proposing an “anti-consumerist consumption”, act as a counterculture in relation to the society that enabled their emergence.